Restorative justice and legal culture - Díaz Gude, Alejandra (Criminology & criminal justice, 2020)
This article explores the question of how to expand restorative justice as a national policy in a country underrepresented by the literature. We maintain that considering legal culture is essential. We identify restorative justice traditions that are characteristic of civil law and common law legal systems, respectively, and compare them with a case study belonging to the former system. We argue that restorative justice practices are shaped by the legal culture, political tradition and criminal justice identity of the system where they develop. We suggest an approach to transferring restorative justice practices based on comparative criminology, restorative justice traditions and legal culture, making a theoretical contribution to the field, as well as having practical implications at the level of public policy design.